Behavior Management: From Theoretical Implications to Practical Applications, 3rd Edition - John W. Maag (Cengage Learning, 2017)
Authored by nationally recognized scholar and behavioral consultant Dr. John W. Maag, this book focuses primarily on students' observable behaviors and the environmental factors that affect their expression. As Maag points out, behavior management is probably one of the most misunderstood concepts in education. Written in a very accessible style, this book demystifies stereotypical beliefs and misconceptions regarding the use of reinforcement, punishment, and self-control. Maag offers clear, but detailed descriptions of proven intervention techniques, supplemented by a range of step-by-step guidelines, sample forms, charts, graphs, and illustrations that assist teachers in implementing the techniques. Although the techniques described in the book are based on a sound theoretical and empirical foundation, the author limits the use of technical jargon and infuses real-life examples and case studies that clarify and illuminate the presentation. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.